Relationship between gut microbiota and Chinook salmon (Oncorhynchus tshawytscha) health and growth performance in freshwater recirculating aquaculture systems - Zhao, Ruixiang; Symonds, Jane E.; Walker, Seumas P.; Steiner, Konstanze; Carter, Chris G.; Bowman, John P.; Nowak, Barbara F. (Frontiers in Microbiology, 2023)
Gut microbiota play important roles in fish health and growth performance and the microbiome in fish has been shown to be a biomarker for stress. In this study, we surveyed the change of Chinook salmon (Oncorhynchus tshawytscha) gut and water microbiota in freshwater recirculating aquaculture systems (RAS) for seven months and evaluated how gut microbial communities were influenced by fish health and growth performance. The gut microbial diversity significantly increased in parallel with the growth of the fish. The dominant gut microbiota shifted from a predominance of Firmicutes to Proteobacteria, while Proteobacteria constantly dominated the water microbiota. Photobacterium sp. was persistently the major gut microbial community member during the whole experiment and was identified as the core gut microbiota for freshwater farmed Chinook salmon. No significant variation in gut microbial diversity and composition was observed among fish with different growth performance. At the end of the trial, 36 out of 78 fish had fluid in their swim bladders. These fish had gut microbiomes containing elevated proportions of Enterococcus, Stenotrophomonas, Aeromonas, and Raoultella. Our study supports the growing body of knowledge about the beneficial microbiota associated with modern salmon aquaculture systems and provides additional information on possible links between dysbiosis and gut microbiota for Chinook salmon.